2020
DOI: 10.13057/biodiv/d210948
|View full text |Cite
|
Sign up to set email alerts
|

Fumigant and feeding deterrent activity of essential oils against Cryptolestes ferrugineus (Stephens) (Coleoptera: Laemophloeidae)

Abstract: Abstract. Ikawati S, Himawan T, Abadi AL, Tarno H. 2020. Fumigant and feeding deterrent activity of essential oils against Cryptolestes ferrugineus (Stephens) (Coleoptera: Laemophloeidae). Biodiversitas 21: 4301-4308. This study aimed to determine the fumigant and antifeedant activity of some plant essential oils against Cryptolestes ferrugineus. Essential oils were extracted from cinnamon (Cinnamomum verum), kaffir lime (Citrus hystrix), citronella grass (Cymbopogon nardus), zodea (Euodia suaveolens), and clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The inhibitory compounds in the essential oil probably interfered with the functioning of the pest's feeding stimulation signals. It may also be said that given the reduction in the relative growth rate of insects, which can be related to a decrease in the relative consumption rate and conversion efficiency of the digested food, the utilization quantity of food also decreased [34]. In general, decreasing nutritional indices result in low biological performance of the pest, especially in terms of food absorption and growth.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibitory compounds in the essential oil probably interfered with the functioning of the pest's feeding stimulation signals. It may also be said that given the reduction in the relative growth rate of insects, which can be related to a decrease in the relative consumption rate and conversion efficiency of the digested food, the utilization quantity of food also decreased [34]. In general, decreasing nutritional indices result in low biological performance of the pest, especially in terms of food absorption and growth.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning C. ferrugineus , Ikawati et al ( 2020 ) observed that adults were more susceptible than larvae after their exposure to Citrus hystrix DC., Euodia suaveolens (Hochr.) Bakh.…”
Section: Discussionmentioning
confidence: 99%
“…where C is the lettuce consumption (g) in the control and T is the lettuce consumption (g) in the treatment [34]. An analysis of variance (ANOVA) was used to analyze the results of the feeding deterrence treatment and the Tukey's test was applied using the SPSS 22 statistical program (IBM, Armonk, NY, USA).…”
Section: Discussionmentioning
confidence: 99%